Clinical profile and treatment outcome in gastrointestinal cancer patients: a single-center experience in Kashmir valley, India - Naqash, Ashfaq Ahmad; Nayak, Bilal Ahmad; Wani, Shahid Bashir; Teli, Mohamad Ashraf (International Journal of Advances in Medicine, 2023)
Background: Gastrointestinal (GI) cancers are one of the common cancers and are associated with significant morbidity and mortality. The present study was conducted to evaluate the treatment outcome of GI cancer patients undergoing follow-up in the oncology OPD of a tertiary care hospital. Methods: Cases previously treated for any GI cancer at one center and coming for follow-up to the hospital were enrolled. Treatment outcome was ascertained in these patients and its relationship with clinical and demographic characteristics of patients at diagnosis were analysed. Results: A total of 68 cases of GI cancers were enrolled with a mean age of 57.44±8.3 years and of 39 (57.35%) were males. The most common site for cancers was oesophagus, stomach, Colo-rectal with 22,20 and 17 cases respectively. Stage II was the most common stage at presentation in 50% cases followed by Stage III in 32.35% of cases. There was significant association between stage at diagnosis with stage I disease at diagnosis significantly related to complete cure. Site of cancer, age and smoking history had no significant correlation with treatment outcome. Conclusions: Diagnosis of GI cancers at early stage was associated with complete cure at follow up. This finding demonstrates the importance of early screening for GI cancers and the need to have robust screening guidelines and improving access to screening with highly valid tests particularly for individuals with high risk features.